Asperpenes D and E from the fungus Aspergillus sp. SCS-KFD66 isolated from a bivalve mollusk, Sanguinolaria chinensis. Issue 2 (1st February 2021) - An, Chang-Liang; Kong, Fan-Dong; Li, Yan; Ma, Qing-Yun; Xie, Qing-Yi; Yuan, Jing-Zhe; Zhou, Li-Man; Dai, Hao-Fu; Yu, Zhi-Fang; Zhao, You-Xing
Abstract: Two new compounds named asperpenes D (1 ) and E (2 ) were isolated from the marine-derived fungus Aspergillus sp. SCS-KFD66. Their structures were determined on the basis of spectroscopic methods. Compound 2 represents the first natural product bearing a 2-substituted-5-oxo-4-phenyl-2, 5-dihydrofuran-3-carboxylic acid skeleton. All the compounds were tested for enzyme inhibitory activity against AChE and α-glucosidase and DPPH radical scavenging activity, respectively.